Pengaruh Konsentrasi Etanol dan Waktu Maserasi terhadap Rendemen, Kadar Total Fenol dan Aktivitas Antioksidan Ekstrak Rumput Laut Padina australis - Annisa Permata Sari; Irmanida Batubara; Muhammad Nursid (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Padina australis seaweed is known to contain active compounds that can be utilized in pharmaceutics and cosmetics. Ethanol concentration and maceration time are thought to affect the concentration of active compounds in the extract. This study aims to determine the effect of ethanol concentration and maceration time on yield, antioxidant activity, and the total phenol content (TPC).  Seaweed samples were taken from Binuangeun waters, Lebak-Banten. Extraction was conducted by maceration method using 0, 40, and 80 % (v/v) ethanol for 8, 16, and 24 hours. Antioxidant activity was carried out using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) test, while the TPC was determined by colorimetry method using FolinCiocalteu reagent. The results showed that the highest extract yield was obtained when using 40 % ethanol and 16 hours maceration time, the highest antioxidant activity was obtained when using  80 % ethanol and 24 hours maceration time, while the highest TPC was obtained when using 40 % ethanol and 8 hours maceration time. Based on this research, the best antioxidant activity of extract was obtained when maceration used 80 % ethanol with a 24-hour maceration time.